Comparison of optical-spectral characteristics of glioblastoma at intraoperative diagnosis and ex vivo optical biopsy - I. D. Romanishkin; T. A. Savelieva; A. Ospanov; N. A. Kalyagina; A. A. Krivetskaya; A. M. Udeneev; K. G. Linkov; S. A. Goryajnov; S. V. Shugay; G. V. Pavlova; I. N. Pronin; V. B. Loschenov (Biomedical Photonics)
The difficulty of intraoperative delineation of glial tumors is due to the peculiarities of their growth along vessels and nerve fibers with infiltration of healthy white matter. Insufficiently complete removal of tumor tissues leads to recurrences, and excessive removal is fraught with neurological complications. Optical spectroscopy methods are characterized by high speed, accuracy and non-invasiveness, which determines the prospects of their use for intraoperative demarcation of the boundaries of such tumors. Fluorescence and diffuse reflectance spectroscopy have found wide application in intraoperative neuronavigation, mainly for detecting the edges of diffuse gliomas. At the same time, in recent years the direction of ex vivo spectral analysis of tumor samples using a combination of various optical spectroscopy methods, including both elastic and inelastic scattering spectroscopy, has been actively developed. Obviously, the ability to obtain spectra intraoperatively and on fresh specimens is different. The present article compares the results of the analysis of optical-spectral characteristics of intracranial tumors at intraoperative diagnosis and ex vivo analysis and proposes a mathematical model for interpretation of the observed dependencies.